HUBUNGAN PERSEPSI IBU RUMAH TANGGA TENTANG BANK SAMPAH DENGAN PARTISIPASI PENGELOLAAN BANK SAMPAH GAWE RUKUN, KOTA TANGERANG - Azrai, Eka Putri; Ernawati, Ernawati; Rizkiani, Santi (Biosfer: Jurnal Pendidikan Biologi, 2016)
Participation of waste bank management is the involvement of physical, mental, and emotional a person to participate actively, contributing, and responsible for the group's goal, in this case the waste bank management activities. One of the factor which participation of ‘Gawe Rukun’ Waste Bank management affect is perception. The purpose of this research was to determine the correlation between housewife’s perception about waste bank and participation of ‘Gawe Rukun’ Waste Bank management. This research was held in RW 01, Kelurahan Kunciran Indah, Tangerang City on April to May 2016. The method used was survey method with correlational study. The sample of this research 151 housewife’s were selected by using simple random sampling. The prerequisite test showed that the data was normal and homogen. Hypothesis test using linear regression test and simple correlation. Regression model obtained Ŷ = 92.511 + 0.737X had a significant and linear correlation. The coefficient of correlation obtained was 0.7502, which means there was a positive relationship between housewife’s perception about waste bank and participation of ‘Gawe Rukun’ Waste Bank management. The coefficient of determination obtained was 0.5628, which means housewife’s perception about waste bank contributed 56.28% to the participation of ‘Gawe Rukun’ Waste Bank management.